Castleman disease presenting as axillary mass: A case report - Aisha Gabra; Mohammed Awad; Walaa Felemban; Ahmad Alawi (Elsevier, 2023)
Background: Castleman disease (CD) is a benign lymphoproliferative disease that results in a massive growth of the lymphoid tissue. CD presents clinically as a localized lymph node group (unicentric) or multifocal (multicentric) across any lymphoid tissue. The variable clinical presentations are based on the location and multicentricity of the lesion. The gold standard diagnostic method of CD is the histological examination. CD has different histological types, including hyaline vascular variant (HVV), plasma cell variant (PCV), and mixed variant. Case presentation: We present a case of a six-year-old Saudi male who had solitary progressive growth of the left axillary lymph nodes for few months without other associated symptoms. Laboratory testing was unremarkable, as well as chest radiographs. Local Ultrasound revealed the lesion to be hypervascular. The patient underwent near-complete surgical excision of the affected lymph nodes. The diagnosis of CD was made upon the histological examination, which revealed a CD hyaline vascular variant. Conclusion: Although CD is a rare clinical entity among the pediatric population. Pediatric surgeons should be aware of the treatment options which must be tailored for each patient based on the lesion's resectability, multicentricity, and presence of systemic inflammatory or compression symptoms.